Anticolonization of Carbapenem-Resistant Klebsiella pneumoniae by Lactobacillus plantarum LP1812 Through Accumulated Acetic Acid in Mice Intestinal - Yan, Rushuang; Lu, Ye; Wu, Xiaoqing; Yu, Peihao; Lan, Peng; Wu, Xueqing; Jiang, Yan; Li, Qi; Pi, Xionge; Liu, Wei; Zhou, Jiancang; Yu, Yunsong (Frontiers in Cellular and Infection Microbiology, 2021)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) is highly prevalent and poses a significant threat to public health. In critically ill patients, gut colonization is considered to be the reservoir of recurrent CRKP infection. Therefore, eliminating CRKP carriage in the intestine is critical for preventing subsequent CRKP infection. In the present study, Lactobacillus plantarum LP1812, a probiotic that can inhibite CRKP in vitro, was used as a candidate probiotic to investigate its efficacy for CRKP anticolonization. Compared with the control, mice fed with 1×10 8 CFU L. plantarum LP1812 exhibited significant CRKP clearance from 1×10 4 CFU/mg to less than 10 CFU/mg in mice feces. Furthermore, 16S RNA gene sequencing revealed that L. plantarum LP1812 modulated mice microbiota by increasing the relative abundance of the genus Halomanas, Blautia, and Holdemania. Further KEGG pathway enrichment analysis revealed that fatty acid-utilizing bacteria, such as acetate-producing Bacteroidetes and Blautia flourished in mice fed with L. plantarum LP1812. Moreover, we found that the concentration of acetic acid was higher in L. plantarum LP1812, which inhibited the growth of K. pneumoniae strains in vitro. Meanwhile, mice intragastrically administered with acetic acid exhibited significantly increased CRKP elimination in vivo. In conclusion, L. plantarum LP1812 is a potential candidate for intestinal CRKP anticolonization by regulating the intestinal microbiota and inhibiting CRKP via increased acetic acid in the intestinal lumen.